Pengaruh Pengetahuan Dasar Perpajakan, Kesadaran Wajib Pajak Dan Konflik Wajib Pajak Terhadap Kepatuhan Wajib Pajak - Ernikawati, Ernikawati; Saputra, Agung Joni; Ria Angriani (Jurusan Akuntansi Politeknik Negeri Padang, 2024)
This research aims to be able to resolve tax problems that always occur in social life in the form of how much influence basic knowledge of taxation, the willingness to sincerely carry out tax obligations and taxpayer problems have on the level of compliance in implementing taxation. The data collection method is by distributing questionnaires to taxpayer respondents and studying things related to taxpayer compliance based on related references, while the results obtained are based on a partial test (Uji_t): basic knowledge of taxation influences tax compliance and taxpayer awareness also has an influence on the level of taxpayer compliance, and there is no impact on taxpayer conflict on the compliance of tax actors. Researchers suggest to Tax Actors in the District Bappeda area. Pasaman is to be able to maximize basic knowledge of taxation, taxpayer awareness and conflict in order to achieve organizational goals and be able to become individuals who are obedient to taxpayers, so as to create an Indonesian society that is obedient to taxes for the progress of the Indonesian nation.